Pentingnya sikap toleransi dalam kehidupan mahasiswa di lingkungan kampus - fitroh, Irsaduddin tsakif (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the importance of tolerance in student life within the campus environment as an effort to create a harmonious and inclusive academic atmosphere. Universities as multicultural interaction spaces bring together students from diverse backgrounds, requiring mutual respect and appreciation for differences. However, in practice, several challenges persist, such as group polarization, stereotypes, low digital literacy, and the suboptimal role of institutions in fostering a culture of tolerance. This research employs a qualitative approach using a literature review method to examine the concept, challenges, and strategies for strengthening tolerance among students. The findings indicate that tolerance is not merely a normative value but must be practically implemented through character education, inclusive social interactions, and institutional policies that support diversity. Therefore, strengthening tolerance is a shared responsibility of all campus stakeholders to create an academic environment that is peaceful, civilized, and grounded in humanitarian values.